Impact Analysis of Total Productive Maintenance Critical Success Factors and Benefits - Díaz-Reza, José Roberto; García-Alcaraz, Jorge Luis; Martínez-Loya, Valeria (Springer International Publishing : Imprint: Springer, 2019)
This book present the state of the art in Total Productive Maintainance (TPM) and its benefits. The authors present a survey applied to 368 manufacturing industries in order to determine their level of execution of TPM. Then a series of causal models are presented. For each model, the authors present a measure of the dependency between the critical success factors and the benefits obtained, allowing industry managers to differentiate between essential and non-essential activities. The content also allows students and academics to obtain a theoretical and empirical basis on the importance of TPM as a lean manufacturing tool in the context of industry 4.0.